Role of Plasma Parameters on the Growth and Field Emission Properties of 2D Graphene Sheet (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
The role of plasma parameters (electron density and temperature, ion density and temperature) on the growth and field emission properties of two dimensional graphene sheet has been theoretically investigated. A theoretical model of charge neutrality, including the kinetics of electrons, negatively and positively charged ions, neutral atoms and the energy balance of various species has been developed. Numerical calculations of the graphene for different plasma parameters (electron density and temperature, ion density and temperature) have been carried out for the typical glow discharge plasma parameters. It is found that the thickness of graphene sheet decreases with plasma parameters and hence the field emission of electrons from the graphene sheet increases. Some of our theoretical results are in compliance with the existing experimental observations.
Keywords: Graphene; Plasma parameters; Thickness; Field emission